Equity in oncology care: addressing disparities in cancer treatment in Georgia - Amany R. Keruakous; Inemesit Akpan; Michael Chahin; Aghapy Kirolos; Mai Keruakous (Frontiers Media S.A., 2024)
This research delves into the disparities in access to oncology care among cancer patients in Georgia, with a specific focus on the distinct challenges faced by African American (AA) individuals compared to non-African American (Non-AA) counterparts. Leveraging data from the 2020 Behavioral Risk Factor Surveillance System (BRFSS) survey and supplementary online resources, the study meticulously examines socioeconomic factors, including income, education, and insurance coverage, which significantly influence the quality of cancer care received. The analysis reveals substantial income gaps between AA and Non-AA patients, underscoring the critical implications for healthcare access. Moreover, AA patients exhibit lower rates of full insurance coverage for cancer-related treatments, posing additional barriers to comprehensive care. By investigating the intersections of race, income, and education, the research aims to pinpoint the root causes of these disparities and proposes evidence-based solutions to address the identified challenges. The ultimate objective is to contribute valuable insights that inform targeted policy recommendations and community-based interventions, fostering a more equitable landscape for oncology care in Georgia. This study seeks to amplify awareness and advocate for tangible measures, striving toward healthcare equity for all cancer patients, irrespective of their racial or socioeconomic backgrounds.